Pemanfaatan Model Modifikasi Blended Learning dalam Pembelajaran Bahasa Bali pada Masa Pandemi Covid-19 - I Nyoman Miarta Putra (Pramana: Jurnal Hasil Penelitian, 2022)
This study aims to share the best learning experiences during the Covid-19 pandemic. Finding a suitable learning model in the midst of this epidemic, the authors innovate because of government policies that cover the implementation of distance learning. Modifying the learning paradigm of Blended Learning is one of them. Blended learning is a type of learning that combines online and face-to-face instruction. Because the face-to-face learning method cannot be implemented directly, changes must be made. Changes are made on both sides, both online and in person. From packaging subject information to offering discussion space for students to explain elements that are not yet understood, the online side is being modified. The study of small test results was used as a starting point for designing virtual